Dasar Pemikiran Filsafati Pengambangan Daerah Pariwisata - Saryani (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2004)
Speaking about tourism it needs to look at the global correlation that the object and tourist. Infrastructure is needed for both. The negative and positive effect found in tourism development. That is why they do have to pay more attention in constructing between tourism and human surrounding and the creative.